Proporcjonalne formuły wyborcze i ich konsekwencje: [Proportional electoral methods and their consequences] (Studia Prawnicze / The Legal Studies, 2010)
Formuła wyborcza to matematycznie określony sposób przekładania liczby otrzymanych głosów na liczbę uzyskanych mandatów przez daną partię. Formuła wyborcza obok okręgów wyborczych oraz progów wyborczych jest jednym z elementów proporcjonalnego systemu wyborczego. W analizach systemu proporcjonalnego przyjmuje się powszechnie, że decydujący wpływ na wynik wyborów ma rozmiar i struktura okręgów wyborczych oraz wysokość progów wyborczych, formuła wyborcza zaś w porównaniu do roli, jaką odgrywają progi wyborcze oraz okręgi wyborcze, ma zwykle znaczenie marginalne. Dodatkowo należy stwierdzić, iż znaczenie formuły wyborczej jest ściśle powiązane z wielkością okręgów wyborczych, wysokością progu ustawowego oraz rozkładem głosów pomiędzy partie. W okręgach małych i średnich, w szczególności o nieparzystej liczbie mandatów, formuła może odgrywać istotną rolę, natomiast w okręgach dużych i narodowych jej znaczenie jest niewielkie. Rozpatrując wpływ wielkości okręgów wyborczych na znaczenie formuły wyborczej, można również stwierdzić, iż w każdym okręgu, niezależnie od jego wielkości formuła decyduje zazwyczaj o tym, komu przypadnie ostatni mandat resztkowy. Electoral method is mathematical mode of translating votes on mandates. Electoral method, together with constituencies and electoral thresholds is one of the element of proportional electoral system. In the surveys of proportional system majority of doctrine assume, that deciding influence on electoral outcomes has magnitude and structure of constituencies and amount of electoral thresholds, while electoral method comparing with aforementioned elements has usually minor meaning. Consequences of choosing electoral method can be however very crucial, sometimes becoming even the most important factor deciding which political parties takes power after elections. This fact create tribute to contemplations on mathematical apparatus and consequences of their applying. In doctrine are proposing different proportional methods. One of the best esteem expert of electoral systems Arend Lijphard, consider that proportional methods should be divided on simple transferable vote system, in which voter vote on individual candidates marking his preferences and party list system, which consist of divisor and quota method. In the article was presenting mathematical and political implication of using particular electoral methods. Author points out that contemporary divisor methods are using commonly than quota methods. It’s ensue mainly form it’s simplicity, endurance on antinomies and easiness in tinkering. Large part of consideration regarded to instrumentalization of electoral methods.